2020
DOI: 10.21272/jnep.12(4).04011
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Initial Stage of the Formation of Ti-Zr-Ni Quasicrystalline Thin Films

Abstract: Using the methods of X-ray diffraction, transmission and scanning microscopy, the features of the initial stage of the formation of the quasicrystalline phase in thin films of Ti-Zr-Ni are studied. The films were obtained by magnetron sputtering of a target of the composition Ti41Zr38.3Ni20.7 (at. %) with deposition on substrates at T  300 K and further vacuum annealing. It was established that immediately after deposition, the films are X-ray amorphous, nanostructured. An analysis of the radial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…It was found that the temperature range of coexistence of these phases with an annealing duration of 1 h extends to 700 C. for an hour at temperatures of 400 (1); 450 (2); 500 (3); 550 (4), and 600 C (5) Using long-term annealing, we found that annealing for 28 h at 470 C leads to the formation of a singlephase quasicrystalline state. An increase in the annealing time to 50 h promotes the appearance of reflection (653) from the approximant phase.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…It was found that the temperature range of coexistence of these phases with an annealing duration of 1 h extends to 700 C. for an hour at temperatures of 400 (1); 450 (2); 500 (3); 550 (4), and 600 C (5) Using long-term annealing, we found that annealing for 28 h at 470 C leads to the formation of a singlephase quasicrystalline state. An increase in the annealing time to 50 h promotes the appearance of reflection (653) from the approximant phase.…”
Section: Resultsmentioning
confidence: 84%
“…As shown in [5,6], in the initial state, immediately after deposition, the films are X-ray amorphous, with a disordered state that is topologically close to icosahedral in the nearest atomic environment. The system of diffraction maxima is formed when the annealing temperature reaches 400 C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we worked out a laboratory technique for the formation of coatings with an icosahedral quasicrystalline phase with a fairly perfect structure. The features of the formation of thin-film coatings with quasicrystalline and crystalline phases of the Ti-Zr-Ni system are described in detail in [9,10]. According to the first experiments on the modification of crystalline Ti-Zr-Ni phases, the formation of the quasicrystalline and crystal-approximant phases occurs as a result of high-speed quenching under pulsed action with a heat load of 0.6 MJ/m 2 .…”
Section: Introductionmentioning
confidence: 99%